HUBUNGAN AKTIVITAS FISIK REMAJA PUTRI TERHADAP KEJADIAN DISMINOREA PADA REMAJA PUTRI USIA 13-15 TAHUN - Marselina Bora; Nila Widya Keswara (Journal of Innovative and Creativity (Joecy), 2026)
Menstrual pain, or dysmenorrhea, is a common reproductive complaint among adolescent girls that can disrupt daily activities. This study examined whether Body Mass Index (BMI), physical activity, and exercise influence dysmenorrhea in 13–15-year-old female students at SMP Bahrul Maghi Tlogomas. Using a cross-sectional design with 30 participants selected through purposive sampling, data were collected via questionnaires and anthropometric measurements, then analyzed using descriptive statistics and multiple linear regression at 5% significance. Results showed that most respondents were 15 years old (50.0%), had light physical activity (56.7%), experienced severe dysmenorrhea (56.7%), had normal BMI (66.7%), and engaged in light exercise (66.7%). Regression analysis revealed that BMI (p=0.036) and exercise (p=0.011) significantly influenced dysmenorrhea. BMI showed a positive relationship (higher BMI = greater pain), while exercise showed a negative relationship (more exercise = less pain). Daily physical activity had no significant effect (p=0.137). In conclusion, BMI and regular exercise significantly affect dysmenorrhea in adolescent girls, whereas general physical activity does not demonstrate a comparable impact